Analysis of Education and Knowledge’s Relationship on Worker Behavior in Waste Processing and Disposal in The Sasirangan Home Industry in Banjarmasin - Skripsiana, Nika Sterina; Heriyani, Farida; Nursantari, Widya (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Sasirangan is a typical cloth from the South Kalimantan which is produced by the Banjarist people in home industries. The production of sasirangan has a very positive impact on the welfare of Banjarist people. However, the processing and liquid waste resulting from the production process can have a negative impact on workers' health and the environment because it contains synthetic dyes and heavy metals. This is caused by poor worker behavior in processing and disposing of liquid waste from sasirangan cloth. Worker behavior can be related to worker education and knowledge. This research aims to analyze the relationship between education, knowledge and the behavior of sasirangan workers in processing and disposing of waste in the home-based sasirangan industry in Banjarmasin. This research is an analytical observational study with a cross sectional approach, carried out at 3 (three) sasirangan production locations: Sungai Jingah, Seberang Masjid Village and Surgi Mufti subdistricts. Sampling used a purposive sampling technique with a sample size of 30 workers. Data analysis was carried out using descriptive and statistical analysis using the Chi Square test with the alternative Fisher Exact Test. The results of data analysis show the p value of the education variables (p=0.032) and knowledge (p=0.049). There is a significant relationship between education and knowledge and worker behavior in processing and disposing of waste in the sasirangan home industry in Banjarmasin. This is in accordance with Lawrence Green's theory, the better the worker's education and knowledge, the better the worker's behavior. The existence of a significant relationship between education and knowledge and workers' behavior in processing and disposing of waste in the sasirangan home industry in Banjarmasin requires follow-up in the form of efforts to increase education and knowledge regarding the processing and disposal of sasirangan waste for workers in the sasirangan home industry in Banjarmasin.